2020
DOI: 10.1080/2331186x.2020.1721642
|View full text |Cite
|
Sign up to set email alerts
|

Crosslinguistic influence on Chinese EFL learners’ acquisition of English finite and nonfinite distinctions

Abstract: English and Chinese have typological differences in finiteness. English has morphological finite and nonfinite distinction, whereas Chinese has no morphological finiteness, and multiple verbs in a clause appear in the form of bare verbs with optional aspectual morphemes, such as the perfective morpheme "le". The current study explores whether and how the lack of morphological finite and nonfinite distinctions in Chinese influences Chinese EFL (English as Foreign Language) learners' acquisition of English finit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 24 publications
(21 reference statements)
0
5
0
Order By: Relevance
“…The latter could potentially account for morpho-syntactic transfer reported in the language production of serializing L1 learners of a non-serializing L2 (e.g. Helms-Park, 2004; Tang, 2018; Yang & Huang, 2009).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The latter could potentially account for morpho-syntactic transfer reported in the language production of serializing L1 learners of a non-serializing L2 (e.g. Helms-Park, 2004; Tang, 2018; Yang & Huang, 2009).…”
Section: Discussionmentioning
confidence: 99%
“…Learners from serializing first languages (L1s) were found to transfer morpho-syntactic features of SVCs (e.g. she went home had dinner ) (Helms-Park, 2004; Tang, 2018; Yang & Huang, 2009) or L1-specific uses (e.g. cook butter melt ) (Helms-Park, 2001; Juffs, 1996) into their L2 English production.…”
Section: Introductionmentioning
confidence: 99%
“…For example, Siu and Ho (2015) found that syntactic skills, or "the recognition and ability to manipulate the grammatical structure of sentences in a language" (Gombert, 1992, cited in Siu & Ho, 2015, affect the reading comprehension of L1 Chinese and L2 English speakers differently across ages and predict L2 comprehension. In addition, Tang (2020) discovered that Chinese EFL students struggle with morphosyntactic transfer from their L1, leading to misuse of bare verbs in L2 English. As L2 proficiency increases, these mistakes in verb forms caused by the typological distinctions between Chinese and English become less common.…”
Section: Language Transfermentioning
confidence: 99%
“…The findings also suggested the influence of L1 background on usage and language learning. Recently, Tang (2020) examined the acquisition and the use of English finite and non-finite verbs among Chinese EFL learners. The participants were divided into three proficiency levels: low, intermediate, and high.…”
Section: Conditional Sentencesmentioning
confidence: 99%